Feeding corn distillers grains as an energy source to gestating and lactating beef heifers: Impact of excess protein on feedlot performance, glucose tolerance, carcass characteristics and Longissimus muscle fatty acid profile of steer progeny. (9th February 2017) - Gunn, Patrick J.; Bridges, Glen A.; Lemenager, Ronald P.; Schoonmaker, Jon P.
Abstract: This study was conducted to determine the impact of dried distiller's grain with solubles (DDGS) from 192 days of gestation through 118 days of lactation on feedlot performance, carcass characteristics, Longissimus muscle (LM) fatty acids and glucose tolerance of male progeny ( n  = 36). Angus‐Simmental heifer dams were fed diets that contained either DDGS (DG) or not (CON) formulated to provide similar daily net energy for gain but differing crude protein. In the feedlot, male progeny were fed a diet devoid of DDGS. An intravenous glucose tolerance test (IVGTT) was performed on a subset of 20 steers prior to harvest. Steers were harvested at a common 12th rib fat depth. Data were analyzed with the GLIMMIX and MIXED procedures of SAS. Performance ( P  ≥ 0.11) and glucose and insulin concentrations during IVGTT ( P  ≥ 0.24) did not differ between treatments. Dressing percentage tended to be greater ( P  = 0.09) in DG than CON progeny, but all other carcass characteristics did not differ ( P  ≥ 0.18). Progeny from DG dams had greater LM 16:2, 18:0, and 20:1 n‐9 concentrations than progeny from CON dams ( P  ≤ 0.02). In conclusion, DDGS are a viable option for gestating and lactating beef cows.